A Continuity Of Care Model Based On Family Empowerment Improves The Family's Ability In Managing Hypertension Among Elderly - Ni Made Riasmini; Komang Ayu Henny Achjar; Tien Hartini; Husnul Khatimah; Erljohn C.Gomez; Riyanto Riyanto (poltekkes kemenkes mataram, 2023)
Family empowerment in the early detection and monitoring of risk factors for hypertension among the elderly is very important because a family is the main support system and the best place and source of happiness for the elderly. Through continuous care (Continuity of Care/CoC), it is hoped that families will be able to assist the elderly in managing hypertension problems, to improve their health status and quality of life among the elderly. This study aims to determine the effect of the CoC model based on family empowerment in increasing family ability (knowledge, attitudes, and behavior) to manage hypertension among the elderly. The research was conducted in Denpasar City with a total sample of 62 people. The research design is a quasi-experiment with a control group design. Data analysis used t-test, Chi-Square, and Multiple Logistic Regression. The results showed that there were significant differences in the ability of families to manage hypertension in the elderly before and after applying the model to the intervention group, namely knowledge (p value=0.019), attitude (p value=0.002), and behavior (p value=0.003). Likewise, significant differences were found in the family's ability to manage hypertension in the elderly after the application of the model between the intervention and control groups, namely knowledge and attitudes (p-value = 0.001) and behavior (p-value = 0.002). The results of the multivariate test found that length of stay had an effect on family attitudes and work on family behavior in managing hypertension in the elderly, apart from the influence of the CoC model. Recommendation: the CoC model intervention based on family empowerment can be used as a form of intervention in empowering family potential so that it can assist the elderly in a community setting.